Polypyrrole-promoted superior cyclability and rate capability of NaxFe[Fe(CN)6] cathodes for sodium-ion batteries. Issue 16 (6th April 2016) - Tang, Yang; Zhang, Wuxing; Xue, Lihong; Ding, Xuli; Wang, Ting; Liu, Xiaoxiao; Liu, Jing; Li, Xiaocheng; Huang, Yunhui
Abstract : The Fe-HCF@PPy composite exhibits superior rate capability and improved cycling stability because of the effects from PPy as both an electronic conductor and a surface protective layer. Abstract : Sodium iron hexacyanoferrate (Fe-HCF) is a potential cathode material for sodium-ion batteries. However, the side reactions in the NaClO4 electrolyte in the charge process over 4.1 V result in structural collapse and low coulombic efficiency during cycling. In this work, we prepared high-quality Fe-HCF microcubes with a size distribution of ∼2 μm and employed conductive polypyrrole (PPy) to wrap the microcubes to form a Fe-HCF@PPy composite. With the coating of PPy, the composite exhibits a discharge capacity of 113.0 mA h g −1 at a current density of 25 mA g −1 and 75 mA h g −1 at 3000 mA g −1 . A greatly improved cycling stability is attained with 79% capacity retention over 500 cycles at 200 mA g −1 . The superior rate capability and excellent cyclability can be ascribed to the effects from PPy as both an electronic conductor to enhance the conductivity and a protective layer to prevent the side reactions.